(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current capacity for implementing diabetes prevention activities at commune health centers (CHCs) of Ha Noi in 2023. Study design: Cross-sectional description. Results: The rate of CHCs with health insurance for examination and treatment of diabetes is 43,52%. The proportion of doctors participating in diabetes diagnosis and treatment at health stations in the area is 17,70%. The percentage of health stations with less than 50% of essential consumable supplies is the highest, accounting for 98,45%. The percentage of health stations with less than 50% of essential medications is also high, at 84,28%. Health stations are not fully equipped with the necessary medications for treatment as stipulated by the Ministry of Health. The main medications provided at these stations are Metformin (34,89%) and Gliclazide (30,57%). Conclusion: Diabetes prevention and management services at grassroots level have not been fully and widely deployed throughout the city. It’s strongly recommended to enhance the availability and readiness of diabetes management services and to invest the essential supplies and medication for diabetes screening, early detection and treatment at primary care, particularly for CHCs in the inner-city and suburban areas.